El The discourse of School Grammar at the beginning of the expansion of the Chilean educational system (1844, 1851) - Narvaja de Arnoux, Elvira; Lauria, Daniela; Cifuentes Sandoval, Juan (Boletín de Filología, 2021)
Chile in the mid-19th century was the moment of affirmation of the national state. In this context, the expansion of the educational system was necessary, which in turn required the production of books for teaching in schools. As far as grammatical discourse was concerned, although it generally showed a remarkable stability, the manual genre of school grammar, on the other hand, was not yet established, nor were the differences between the texts for the different school levels (primary and secondary) clearly established. This instability explains the vacillations exhibited by the texts of the period and the various theoretical, methodological and discursive options that are set. In this paper, we focus on two early school grammars: Fernando Zegers Tratado de gramática castellana dedicado a la juventud americana de los pueblos que hablan la lengua española (1844) and Andrés Bello’s Gramática castellana para uso de las escuelas (1851). The first precedes Bello’s consecrated grammar of 1847; the second summarizes how Bello believes grammar should be taught to children. While Zegers had teaching experience, Bello was the great grammarian who repeatedly reflected on the importance of teaching grammar in elementary schools, as shown in several notes he wrote and in the typographical separation he designed for his key work of 1847. In particular, we will analyze from the glottopolitical approach how one and the other author resolve in their respective works the tensions between the grammatical tradition and the new space of school circulation, and between the legitimized grammatical knowledge and the specific objectives of teaching. In this sense, we observe three aspects that operate differently. First, the parts of the traditional study of grammar that are consigned (analogy, syntax, orthography, orthology, prosody, metrics). Second, the type of discourse adopted, which accentuates, with greater or lesser emphasis, the dogmatic tone based on the presence of normative sequences rather than reasoned exposition. Finally, the function of the examples that in one case privilege a religious formation and in the other lead to an indoctrination that contemplates the integral development of the citizen. In summary, we perceive two opposing models of grammar teaching: while Zegers is in line with classical studies that focus on teaching the language in order to reach the written text; Bello, on the other hand, is concerned with promoting grammatical reflection. Both models expose, in addition, different configurations of collective imaginaries and social projects from their discourse on language.